If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 12) = (4x + -24) Reorder the terms: (12 + x) = (4x + -24) Remove parenthesis around (12 + x) 12 + x = (4x + -24) Reorder the terms: 12 + x = (-24 + 4x) Remove parenthesis around (-24 + 4x) 12 + x = -24 + 4x Solving 12 + x = -24 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 12 + x + -4x = -24 + 4x + -4x Combine like terms: x + -4x = -3x 12 + -3x = -24 + 4x + -4x Combine like terms: 4x + -4x = 0 12 + -3x = -24 + 0 12 + -3x = -24 Add '-12' to each side of the equation. 12 + -12 + -3x = -24 + -12 Combine like terms: 12 + -12 = 0 0 + -3x = -24 + -12 -3x = -24 + -12 Combine like terms: -24 + -12 = -36 -3x = -36 Divide each side by '-3'. x = 12 Simplifying x = 12
| -10=2x+9 | | 0=5x^2+12x+4 | | (54-18/3)+(-6)= | | 13x-35=8x+30 | | 4sin^2=2cos+1 | | 27.95*4+0.29x=150 | | 2x+35=x-27 | | 3x+19=4x+8 | | 10(2+4)-3(2-4)=3(2-2)+3(2-1) | | 5y-(5)+5=0 | | 6x+16=2-8x | | 7(x+9)+4=9x-2(x-4) | | 4x-(-2)=-8-2 | | 5(5)-x+5=0 | | 15-x+6-2x=12 | | 8b^5-58b^3+50b=0 | | 8b^5-58b^3+50b=0 | | 5u+1=8u-2 | | k^2-20k-52=-8 | | 4(u+1)u=8(u-1)+6 | | 2x+4(47-x)=138 | | -7k-3=-2k+17 | | 5y+3=5y | | 8x+7=-7+6x+20 | | 3m-16= | | 5(-4x+20)-x+5=0 | | t^5-10t^3+9t=0 | | 4r+5=19r+10 | | t^5-10t^3+9t=0 | | -4y+8xy+x-11xy-8x= | | t^5-10t^3+9t=0 | | 4r+5=19r+10 |